Analysis of English Learning Strategies of Children of Immigrant Workers in Informal Schools in Malaysia - Diyah Atiek Mustikawati; Niken Reti Indriatuti (Universitas Nahdlatul Wathan Mataram, 2023)
Education is the main key that someone needs, to penetrate the gates of educational institutions to get a good education and a brighter future. It should be noted that good education is not only obtained in formal schools but the same opportunities can also be achieved by the children of immigrant workers in Malaysia in an informal school. Although habituation is not always easy, especially in learning English. For this reason, there are many learning strategies that they use including (1) Memory Strategies (2) Cognitive Strategies (3) Compensation Strategies (4) Metacognitive Strategies (5) Affective Strategies (6) Social Strategies. This study aims to analyze the children's learning strategies in learning English, and with quantitative research methods and clear presentations, the author will describe the results of the strategy analysis. The results of this study are in the form of elaboration of percentages to find the strategies most used by students. In conclusion, the writer wants to convey to readers that every child has a different way of learning something.